Comparison of viable plate count, turbidity measurement and real‐time PCR for quantification of Porphyromonas gingivalis. (21st November 2014) - Clais, S.; Boulet, G.; Van kerckhoven, M.; Lanckacker, E.; Delputte, P.; Maes, L.; Cos, P.
Abstract The viable plate count (VPC) is considered as the reference method for bacterial enumeration in periodontal microbiology but shows some important limitations for anaerobic bacteria. As anaerobes such as Porphyromonas gingivalis are difficult to culture, VPC becomes time‐consuming and less sensitive. Hence, efficient normalization of experimental data to bacterial cell count requires alternative rapid and reliable quantification methods. This study compared the performance of VPC with that of turbidity measurement and real‐time PCR (qPCR) in an experimental context using highly concentrated bacterial suspensions. Our TaqMan‐based qPCR assay for P. gingivalis 16S rRNA proved to be sensitive and specific. Turbidity measurements offer a fast method to assess P. gingivalis growth, but suffer from high variability and a limited dynamic range. VPC was very time‐consuming and less repeatable than qPCR. Our study concludes that qPCR provides the most rapid and precise approach for P. gingivalis quantification. Although our data were gathered in a specific research context, we believe that our conclusions on the inferior performance of VPC and turbidity measurements in comparison to qPCR can be extended to other research and clinical settings and even to other difficult‐to‐culture micro‐organisms. Significance and Impact of the Study Various clinical and research settings require fast and reliable quantification of bacterial suspensions. The viable plate count method (VPC) is generally seen as 'the gold standard' for bacterial enumeration. However, VPC‐based quantification of anaerobes such as Porphyromonas gingivalis is time‐consuming due to their stringent growth requirements and shows poor repeatability. Comparison of VPC, turbidity measurement and TaqMan‐based qPCR demonstrated that qPCR possesses important advantages regarding speed, accuracy and repeatability.